The cost of equity capital in stock portfolios listed on the warsaw stock exchange using the classic CAPM - Stanislaw Urbanski (e-Finanse: Financial Internet Quarterly, 2019)
This work is an attempt to estimate the cost of equity capital characteristic among portfolios of companies listed on the Warsaw Stock Exchange in the years 1995-2017. To this end, the classic CAPM is used to estimate the cost of risk. Model tests are based on 252 monthly returns. In order to assess the errors of cost of capital estimation, the bootstrap method is used. The estimated cost of capital refers to the project portfolio with real options on these projects. Stock returns are generated not only by the companies implementing projects but also through real options modifying these projects. The estimated cost of capital can be a valuable indicator for portfolio managers. Also, it can be an approximate indicator for making decisions on the implementation of new investment projects. The estimated cost of capital assumes the highest values for value portfolios. The estimated cost of capital assumes the small values for growth portfolios.
Keywords: G11; G12; 330; ICAPM; Cost of capital; Risk premium